2024
DOI: 10.7759/cureus.55913
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Social Determinants of Health on Outcomes Among Individuals With HIV and Heart Failure: A Literature Review

Pawel Borkowski,
Natalia Borkowska

Abstract: This narrative review examines the complex interplay between social determinants of health (SDoH) and the outcomes for individuals living with human immunodeficiency virus (HIV) and heart failure (HF), two conditions that pose significant socioeconomic burdens globally. With millions affected by these conditions, the review delves into how socioeconomic status, education, geography, and immigration status influence health outcomes. It further explores the exacerbating roles of stigma and mental health issues, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 47 publications
0
1
0
Order By: Relevance
“…Research also shows that rural populations often face higher mortality rates and poorer health outcomes due to limited access to healthcare. For instance, a study by Baljepally and Wilson found higher cardiovascular disease rates in rural areas, while another by Borkowski and Borkowska highlighted challenges in HIV treatment access for rural residents [20,21]. These examples underscore the need for targeted interventions to address urban-rural health disparities across various diseases.…”
Section: Discussionmentioning
confidence: 99%
“…Research also shows that rural populations often face higher mortality rates and poorer health outcomes due to limited access to healthcare. For instance, a study by Baljepally and Wilson found higher cardiovascular disease rates in rural areas, while another by Borkowski and Borkowska highlighted challenges in HIV treatment access for rural residents [20,21]. These examples underscore the need for targeted interventions to address urban-rural health disparities across various diseases.…”
Section: Discussionmentioning
confidence: 99%